THE TOURIST EXPERIENCE AT THE KHAJURAHO DANCE FESTIVAL 2024 - Anshima Srivastava, Prof. Devesh Nigam (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
Every year, the ancient town of Khajuraho, India, hosts the Khajuraho Dance Festival, a special venue for exhibiting classical dance styles and honoring the area's rich cultural legacy. This paper investigates the 2024 festival from the perspective of tourists, looking at visitors' expectations, motivations, and general happiness. The study used a mixed-methods approach to examine qualitative and quantitative data, offering valuable insights into the festival's effects on local communities and cultural tourists. The results underscore the importance of the festival in augmenting the visitor experience and advancing sustainable tourism in Khajuraho.